Nodulo-ulcerative Tuberculosis of the Glans Penis—A Case Report and a Discussion on Nomenclature of Genital Tuberculosis - Deb, Samujjala (Indian J Dermatol, 2015)
Lupus vulgaris is a chronic paucibacillary form of cutaneous tuberculosis occurring in a person with a moderate to high degree of immunity. It commonly occurs over the buttocks and trunk in India. Involvement of the genitalia is uncommon, and lesions involving the penis, extremely rare with few cases reported worldwide. There also exists a confusion regarding nosology of tuberculosis of the genitalia. A brief discussion and review of literature are being discussed along with the report of a case of genital tuberculosis involving the glans penis.